The Role of Blackboard Technology for School System and Processes Transformation in Nigerian Tertiary Institutions - Idris , Muhammad Kabir; Dattijo Abubakar, Yahaya; Adamu Ahmed, Aminu (Lafadz Jaya Publisher, 2025)
This study aims to explore the role of Blackboard technology in transforming the school system and processes in Nigerian tertiary institutions. Blackboard technology is a learning management system that provides a virtual platform for educators and students to interact and engage in the learning process. The study begins by examining the current state of the Nigerian tertiary education system and the challenges it faces. These challenges include limited access to quality education, outdated teaching methods, and inadequate infrastructure. The introduction of Blackboard technology has the potential to address these challenges and bring about much-needed transformation. The study then delves into 25 various studies right from twenty years back that pave the ways in which Blackboard technology can transform the school system and processes. Firstly, benefits of blackboard technology in Nigerian tertiary institutions, allowing students to access educational resources and participate in classes from anywhere, at any time. This is particularly beneficial for students in remote areas or those with limited mobility. Secondly, addressing infrastructure and technological challenges in Nigeria. By providing a platform for sharing course materials, submitting assignments, and engaging in discussions. This enhances collaboration and interaction, leading to a more engaging and interactive learning experience. Furthermore, Blackboard technology supports personalized learning. It allows educators to create customized learning paths and tailor educational content to individual students' needs and learning styles. This promotes student-centered learning, encouraging active participation and improving learning outcomes.